2010
DOI: 10.1007/s10661-010-1743-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of spatio-temporal land cover changes for hydrological impact assessment within the Nyando River Basin of Kenya

Abstract: The spatio-temporal changes in the land cover states of the Nyando Basin were investigated for auxiliary hydrological impact assessment. The predominant land cover types whose conversions could influence the hydrological response of the region were selected. Six Landsat images for 1973, 1986, and 2000 were processed to discern the changes based on a methodology that employs a hybrid of supervised and unsupervised classification schemes. The accuracy of the classifications were assessed using reference datasets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…A widespread problem identified in the region was the vast land cover degradation within the riparian upstream catchments important in the sustainability of the existing water resources. The Nyando River Basin (NRB) with its headwaters in the endangered Mau Forest Complex (MFC) region in particular was seen to epitomize the degradation because of its physical susceptibility, coupled with the existence of poor land and water management strategies (Krhoda, ; Olang et al ., ). Previous studies of the NRB involving change detection from time‐series Landsat satellite images have revealed varying proportions of spatio‐temporal changes.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…A widespread problem identified in the region was the vast land cover degradation within the riparian upstream catchments important in the sustainability of the existing water resources. The Nyando River Basin (NRB) with its headwaters in the endangered Mau Forest Complex (MFC) region in particular was seen to epitomize the degradation because of its physical susceptibility, coupled with the existence of poor land and water management strategies (Krhoda, ; Olang et al ., ). Previous studies of the NRB involving change detection from time‐series Landsat satellite images have revealed varying proportions of spatio‐temporal changes.…”
Section: Introductionmentioning
confidence: 97%
“…The lower parts of the basin, however, exhibited subtle land cover fluctuations that varied between agriculture and grasslands on seasonal basis. From the land cover conversion patterns, it is concluded the basin was more likely to be converted into an agricultural area in the near future if the land cover change trends continued unabated (Rambaldi et al ., ; Olang et al ., ). Further research studies using hydrological models have also revealed the changing response of the Nyando basin, particularly during storm events of the long rainy season (LRS) (Opere and Okello, ; Olang and Fürst, ).…”
Section: Introductionmentioning
confidence: 97%
“…Land cover features are part of the ecosystem equilibrium, and any environmental changes that affect them is worth studying [1]-particularly due to the increasing expansion of urban areas which causes permeable land reduction and increased flooding [2,3]. It is widely accepted that the magnitude and frequency of floods is currently increasing [4].…”
Section: Introductionmentioning
confidence: 99%
“…Two headwater tributaries of the Mara, the Nyangores and Amala Rivers, descend from the Mau escarpment, one of Kenya's five so‐called water towers. The Mau Forest, which crowns the escarpment, has been subject to an alarming rate of deforestation in recent years (Baldyga et al ., ) that appears to have affected the hydrology of a number of basins (Krhoda ; Raini, ; Olang et al ., ), including possibly the Mara. Historic hydrometeorological conditions in the Nyangores and Amala basins have been studied (Melesse et al ., ), but without consideration of temporal change and variability.…”
Section: Introductionmentioning
confidence: 99%